Water Allocation Based on Source Capacity, Non-Revenue Water (NRW), and Customer Priority at PT Air Minum Giri Menang Perseroda Mataram." - Nurul Hidayati; I Wayan Yasa; Hartana Hartana (Eduvest - Journal of Universal Studies, 2026)
The operational reliability condition of the pipeline network in the West Lombok Regional Government Housing Area is currently facing technical challenges in maintaining the continuity of flow to the downstream side of consumers. Based on preliminary studies and analysis of global water balance conducted using official annual volume data from agencies for the period of 2024, the level of network leakage or Non-Revenue Water (NRW) in the residential cluster is calculated to have exceeded 40%. This study aims to determine the effective capacity of the system in meeting the water needs of each zone through a tiered allocation simulation based on the priority order of the AHP-SAW method. The results of the analysis show that the water source capacity (safe yield) is still within safe limits for the potential for aquifer recharge. Real production reached 132,095,000 m³/year or 83.77% of installed capacity, indicating that the pump has been operating close to its optimal capacity. Meanwhile, the ecological exploitation index of 41.89% shows that groundwater utilization is still within safe and sustainable limits. The existing conditions of NRW show that there is a variation in the rate of water loss in each service zone. Zone 1 has an estimated NRW of 48.690%, followed by zone 2 and zone 3. The simulation results show that the effective capacity has not been able to meet all the water needs of each zone at the same time.